Seismic Response of R.C. Structures with Different Steel Bracing Systems Considering Soil - Structure Interaction: Enhancing the seismic performance of R.C. structures through steel bracing and soil-structure interaction (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this study the seismic response of reinforced concrete structure using steel bracing considering soil structure interaction to increase the horizontal stability of structure and rigidity of the structure. In which it is assumed that the building is fixed at it bases, but in reality the soil medium allows movement to some extent due to its property to deform. Therefore, this may decrease the stiffness of the structure and hence may increase the natural periods of the system. Thus, the process in which soil influences the movement of the structure and further this movement of structure influence the response of the soil is termed as Soil-Structure Interaction. Using different bracing X, V, Chevron bracings in different positions and with effect of SSI and without of SSI to strengthening the R.C. structure.